Intraexaminer and interexaminer reliability of mastoid fossa readings using a temporal artery thermometer - Seay, Claudia (Elsevier, 2007)
OBJECTIVE: The temperature of the mastoid fossa region has been measured by chiropractors since the 1950s using various instruments. The reliability of the procedure is largely unknown for the various instruments used for this purpose. This study assessed the reliability of a thermal instrument designed to measure forehead temperature while having an alternate landmark as the mastoid fossa. METHODS: Thirty students were recruited to participate. Three blinded examiners twice scanned each student with the temporal artery thermometer. Intraexaminer and interexaminer reliability was assessed using the intraclass correlation coefficient. Differential margins of error were also calculated. RESULTS: Intraexaminer reliability was acceptable in 6 of 6 assessments, whereas interexaminer reliability was acceptable in 3 of 4 assessments. The maximum mean differential margin of error was 0.54 for intraexaminer reliability and 0.46 for interexaminer reliability. DISCUSSION: Combining the mean maximum differential margin of error for intraexaminer (0.54°) and interexaminer (0.46°) and then averaging these 2 ([0.54 + 0.46] / 2) results in a maximum mean differential margin of error of 0.50°. CONCLUSION: In this study, intraexaminer reliability ranged from fair to strong. For these examiners, fossa differentials of 0.5 can be considered within the margin of error.